Life-stages, exploitation status and habitat use of Lutjanus goreensis (Perciformes: Lutjanidae) in coastal marine environments of Lagos, SW Nigeria - Fakoya, Kafayat A. (2015)
The Gorean snapper, Lutjanus goreensis is an important component of artisanal fisheries and trawl landings in the Gulf of Guinea. Despite its economic importance, there is a dearth of information on size structure and life history strategies of the species. Therefore, the objectives of this study were to provide baseline data on the life stages, exploitation status and habitat use for the species in Nigeria. Monthly samples were obtained from artisanal and trawl catches in Five Cowrie Creek and Lagos coastal waters between December 2008 and December 2010, respectively. Length-frequency distributions of the fishes caught were analysed to provide preliminary information on mean and modal lengths at capture and life - history strategies based on habitat use and estuarine-dependency for L. goreensis. A total of 822 specimens of L. goreensis were collected from Five Cowrie Creek, while 377 specimens were collected from Lagos coastal waters. Total length varied between 7.90-34.90cm for estuarine samples and from 21.90-56.10cm for marine samples. Length-frequency histograms showed polymodal size distributions in estuarine and marine samples. Length-frequency distributions of L. goreensis showed a high abundance of juveniles (<20cm) and sub-adults (20-35cm) which accounted for 84.1% and 68.4% of estuarine and marine samples examined, respectively. For the estuarine samples, fish in modal length class of 13.00-13.99cm were the most exploited while in marine samples, length classes of 29.00-30.99cm and 31.00-32.99cm constituted the most frequently exploited fishes. Increase in total lengths from the creek (mean±SD; 16.19±3.73cm) to the marine habitat (32.89±6.14cm) indicated ontogenetic shift in habitat use. Occurrence of a predominant juvenile population in Five Cowrie Creek by L. goreensis suggests estuarine-dependency and is indicative of a temporary juvenile habitat or a migratory corridor. In conclusions, data from the presently reported study and previous studies demonstrated that juvenile L. goreensis displays estuarine dependency and habitat flexibility. Hence, this underscores the importance of preserving estuarine environments as essential fish habitats to prevent overfishing. The study also concludes that the species is vulnerable to recruitment overfishing in the marine environment especially as a consequence of shrimping. Consequently, it advocates for ban on all fishing activities during peak spawning periods in breeding grounds and shrimp ground assemblage.